PERANCANGAN ENTERPRISE ARCHITECTURE PADA PENGELOLAAN SURAT MENGGUNAKAN STANDAR FEAF - Salsa Tini Kareksi (Universitas Teknokrat Indonesia, 2021)
At the Sukabumi District Transportation Office, letter management activities are carried out in a semi-computerized manner, namely using an agenda book and the Microsoft Excel application, however, although letter management activities are computerized, there are several obstacles, namely frequent errors in letter data collection and loss of letter data. . Broadly speaking, the loss of letter data occurs in incoming mail data in 2019, the loss of incoming mail data reaches 50%, while errors in the data collection of letters occur in outgoing mail data, errors in data collection almost occur every year and reach 10-40% so that it can affect making reports on the number of letters. Because of these various problems, the researcher will design an enterprise architecture for letter management using the FEAF (Federal Enterprise Architecture Framework) standard in the Sukabumi Dis-trict Transportation Service. This research will produce a framework (blueprint) which is expected to be a source of reference in implementation and to facilitate the management of incoming and outgoing mail by considering aspects of business, information, applications and technology